In early rheumatoid arthritis, anticitrullinated peptide antibodies associate with low number of affected joints and rheumatoid factor associates with systemic inflammation - Pertsinidou, Eleftheria; Saevarsdottir, Saedis; Manivel, Vivek Anand; Klareskog, Lars; Alfredsson, Lars; Mathsson-Alm, Linda; Hansson, Monika; Cornillet, Martin; Serre, Guy; Holmdahl, Rikard; Skriner, Karl; Jakobsson, Per-Johan; et al. (Annals of the rheumatic diseases, 2024)
ObjectivesTo investigate how individual rheumatoid arthritis (RA) autoantibodies associate with individual signs and symptoms at the time of RA diagnosis.MethodsIgA, IgG, IgM rheumatoid factor (RF), antibodies against cyclic citrullinated peptide version 2 (anti-CCP2) and 16 individual antibodies against citrullinated protein (ACPA) reactivities were analysed centrally in baseline sera from 1600 patients with RA classified according to the 1987 American College of Rheumatology (ACR) criteria. These results were related to C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), number of swollen and tender joints (SJC and TJC), 28-joint disease activity scores (DAS28 and DAS28CRP), global disease activity evaluated by the patients and Health Assessment Questionnaire, all obtained at baseline.ResultsIndividually, all autoantibodies except immunoglobulin G (IgG) RF associated with low SJC and TJC and with high ESR. In IgM RF-negative patients, ACPA associated strictly with low number of swollen and tender joints. This association persisted in multiple regression and stratified analyses where IgM and IgA RF instead associated with inflammation expressed as ESR. Among subjects without any ACPA peptide reactivity, there was no association between RF isotypes and ESR. The effect of RF on ESR increased with the number of ACPA reactivities, especially for IgM RF. In patients fulfilling the 1987 ACR criteria without taking RF into account, associations between IgM RF and high ESR, as well as between ACPA and low joint counts, remained.ConclusionWhereas ACPA associate with low counts of affected joints in early RA, RF associates with elevated measures of systemic inflammation in an ACPA-dependent manner. This latter finding corroborates in vitro models of ACPA and RF in immune complex-induced inflammation. These phenotypic associations are independent of classification criteria.